2018
DOI: 10.1111/liv.13687
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐492 regulates metastatic properties of hepatoblastoma via CD44

Abstract: We identified miR-492 and its target CD44 as regulators of a number of biological features important for malignancy and metastasis. Furthermore, we demonstrated the diagnostic and prognostic potential of miR-492, a promising novel therapeutic target and biomarker for hepatoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…By contrast, miR-492 is highly expressed in hepatoblastoma tissues and cell lines. Retinal cells in patients with hepatoblastoma who present with high miR-492 levels exhibit more high-risk or aggressive behaviours than those with low miR-492 levels (26,27). miR-492 is also upregulated in hepatic cancer, and this upregulation is strongly associated with poor survival (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, miR-492 is highly expressed in hepatoblastoma tissues and cell lines. Retinal cells in patients with hepatoblastoma who present with high miR-492 levels exhibit more high-risk or aggressive behaviours than those with low miR-492 levels (26,27). miR-492 is also upregulated in hepatic cancer, and this upregulation is strongly associated with poor survival (23).…”
Section: Discussionmentioning
confidence: 99%
“…In clear cell renal cell carcinoma, miR-492 restoration restricts cell proliferation and invasion, induces cell apoptosis and promotes cell adhesion (22). Nonetheless, miR-492 serves oncogenic roles in hepatoblastoma by promoting cell proliferation, anchorage-independent growth and metastasis (26). In breast cancer, ectopic miR-492 expression significantly promotes cell proliferation and anchorage-independent growth (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No previous studies have reported on the regulatory roles of miR-1224-5p, miR-492, or miR-135b-5p in chondrosarcoma cells, 23,[25][26] yet some published documents have shown that miR-1224-5p, miR-492, and miR-135b-5p may play important roles in the proliferation, invasion, and metastasis of nonchondrosarcoma tumors. [13][14][15][16][17][18][19][20][21][22] To the best of our best knowledge, miR-6839-5p has not been reported in the literature. In the current study, we hypothesized that miR-1224-5p, miR-492, miR-135b-5p, and miR-6839-5p might play vital roles in how SW1353 cells respond to irradiation with 125 I seeds.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Some studies have demonstrated that miRNAs play an important role in the proliferation, invasion, and metastasis of cancer. [13][14][15][16][17][18][19][20][21][22] In recent years, several studies have assessed the roles of miRNAs in chondrosarcoma, yet none of the findings have focused on the effects of 125 I seeds irradiation exposure on the miRNAs expression profiles of conventional chondrosarcoma cells. 12,[23][24][25][26][27] In the current study, we developed a new in vitro 125 I seed irradiation model to study the effects of 125 I seed irradiation on the proliferation of grade II chondrosarcoma SW1353 cells.…”
Section: Introductionmentioning
confidence: 99%